2013
DOI: 10.1016/j.apenergy.2012.12.072
|View full text |Cite
|
Sign up to set email alerts
|

Methane potentials of the Swedish pulp and paper industry – A screening of wastewater effluents

Abstract: With the final aim of reducing the energy consumption and increase the methane production at Swedish pulp and paper mills, the methane potential of 62 wastewater effluents from ten processes at seven pulp and/or paper mills (A-G) was determined in anaerobic batch digestion assays. This mapping is a first step towards an energy efficient and more sustainable utilization of the effluents by anaerobic digestion, and will be followed up by tests in lab-scale and pilot-scale reactors. Five of the mills produce kraf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 21 publications
2
40
0
Order By: Relevance
“…It can be observed that R1 had the highest yield (324 mL CH 4 / gCOD) which is attributed to the higher VFA content (acetic acid) available in the EC substrate. Similar results for NSSC evaporator condensates ranging from 140 to 340 mL CH 4 /gCOD were found in other studies (Meyer and Edwards, 2014;Ekstrand et al, 2013;Arshad and Hashim, 2012). A common setback of easily degradable substrates is the possible accumulation of intermediate products through the anaerobic degradation pathway.…”
Section: Methane Potentialsupporting
confidence: 90%
See 1 more Smart Citation
“…It can be observed that R1 had the highest yield (324 mL CH 4 / gCOD) which is attributed to the higher VFA content (acetic acid) available in the EC substrate. Similar results for NSSC evaporator condensates ranging from 140 to 340 mL CH 4 /gCOD were found in other studies (Meyer and Edwards, 2014;Ekstrand et al, 2013;Arshad and Hashim, 2012). A common setback of easily degradable substrates is the possible accumulation of intermediate products through the anaerobic degradation pathway.…”
Section: Methane Potentialsupporting
confidence: 90%
“…Methanogenic bacteria can directly convert acetic acid into methane and carbon dioxide avoiding the initial hydrolysis step which is the ratelimiting step in the anaerobic digestion process. Different studies have investigated the anaerobic treatment of evaporator condensate (Ekstrand et al, 2013;Silva et al, 2009;Ferguson and Benjamin, 1985) and found that in spite of a general good running of the anaerobic digestion of this substrate, by itself it may cause inhibition and stability problems. Silva et al (2009) also recognized that anaerobic treatment when an external carbon source is added to the reactor, specifically at high organic loads (2 kg COD/m 3 d À1 or higher) was beneficial and achieved a steady state of COD evolution.…”
Section: Introductionmentioning
confidence: 99%
“…20. Due to the value of methane as a fuel, and perhaps also the importance of avoiding its release into the atmosphere (Weiland 2010), much research has been devoted to its generation during anaerobic treatment of P&P mill wastewater (Maat and Habets 1987;Korczak et al 1991;Minami et al 1991;Sierraalvarez et al 1991;Vidal et al 1997;Kortekaas et al 1998;Ahn and Forster 2002;Buzzini and Pires 2007;Yilmaz et al 2008;Tabatabaei et al 2010;Lin et al 2011;Saha et al 2011;Elliott and Mahmood 2012;Bayr et al 2013;Ekstrand et al 2013;Hagelqvist 2013;Hassan et al 2014;Meyer and Edwards 2014;Larsson et al 2015). …”
Section: Principles Of Anaerobic Treatmentmentioning
confidence: 99%
“…This is a very important issue because the kraft wood pulping efflu ent is alkaline [142] which may lead to the failure of the system. Moreover, the ECF acidic effluents from the KP mills have been shown to be very toxic to the AD microorganisms [143] and this can directly affect the methane production from such effluents. Gao et al (2010) [111] indicated that although a pH shock of 8.0 had no important adverse effects on the performance of a SAnMBR in terms of COD removal, biogas production and membrane filtra tion, the long lasting negative effects of pH shocks of 9.1 and 10.0 were significant.…”
Section: Other Types Of Ad Reactorsmentioning
confidence: 99%